Austritt einzelner Länder aus der Währungsunion: Ein Szenario - Gerd Grözinger (Wirtschaftsdienst, 2014)
Tritt ein Mitgliedsland aus der Europäischen Währungsunion aus, hat das Folgen für die Gemeinschaft. Einige Wissenschaftler fürchten, dass in diesem Fall die Eurozone Schaden nimmt oder sogar zusammenbricht. Wie ein erfolgreicher Austritt organisatorisch und institutionell gestaltet werden kann, schildert der Autor am Beispiel Frankreich. – – The exit of a member state from the eurozone is often depicted as a catastrophic event that would lead to uncontrollable havoc in the financial markets. In this contribution, an alternative scenario is developed based on a consensual understanding. It describes a multi-year transition period during which all member states payments were automatically realised on the basis of a basket consisting of the euro and the new currency. In the remaining eurozone countries, the relative weight of the euro would increase over time, while it would decrease in the exit state. The hope is that the possibility of a smooth exit path would increase the bargaining power to change the governance rules of the eurozone.
Keywords: E42; E58; H63; 330; Eurozone; EU-Mitgliedschaft; Frankreich